2003
DOI: 10.3201/eid0908.020748
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Non–Babesia divergensOrganism Causing Zoonotic Babesiosis in Europe

Abstract: In Europe, most reported human cases of babesiosis have been attributed, without strong molecular evidence, to infection with the bovine parasite Babesia divergens. We investigated the first known human cases of babesiosis in Italy and Austria, which occurred in two asplenic men. The complete 18S ribosomal RNA (18S rRNA) gene was amplified from specimens of their whole blood by polymerase chain reaction (PCR). With phylogenetic analysis, we compared the DNA sequences of the PCR products with those for other Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
289
2
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(309 citation statements)
references
References 25 publications
(30 reference statements)
6
289
2
12
Order By: Relevance
“…In contrast, Babesia sp. EU1 which has repeatedly been identified in game or in ticks in Europe (Casati et al, 2006;Duh et al, 2005a;Duh et al, 2005b;Hilpertshauser et al, 2006 and this work) and which also has been reported in three splenectomized human patients (Haselbarth et al, 2007;Herwaldt et al, 2003), differs by 3% in this gene sequence. The analyses of part of the 28S rRNA gene and of the more variable locus, the rDNA ITS, revealed again a high similarity, but the isolates from cattle could clearly be differentiated from those of free-ranging ruminants (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, Babesia sp. EU1 which has repeatedly been identified in game or in ticks in Europe (Casati et al, 2006;Duh et al, 2005a;Duh et al, 2005b;Hilpertshauser et al, 2006 and this work) and which also has been reported in three splenectomized human patients (Haselbarth et al, 2007;Herwaldt et al, 2003), differs by 3% in this gene sequence. The analyses of part of the 28S rRNA gene and of the more variable locus, the rDNA ITS, revealed again a high similarity, but the isolates from cattle could clearly be differentiated from those of free-ranging ruminants (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…In Europe, Babesia infections are caused mainly by Babesia divergens (142). The majority of cases described occurred in splenectomized patients (166).…”
Section: Other Parasitic Infectionsmentioning
confidence: 99%
“…Babesia sp. EU1 is closely related to Babesia odocoilei (a parasite of white-tailed deer) and based on a 31-nucleotide difference over the complete 18S rRNA gene sequence has been placed phylogenetically in a sister group with B. divergens (Herwaldt et al 2003). Detection of Babesia sp.…”
Section: Introductionmentioning
confidence: 99%
“…A novel species recently described in Europe is Babesia sp. EU1, proposed as Babesia venatorum (Herwaldt et al 2003). Roe deer are thought to be the natural host of this potentially zoonotic species.…”
Section: Introductionmentioning
confidence: 99%